Pete the cat screams for ice cream! eaudiobook - Dean, James (Pete the Cat., 2024)
I scream! You scream! Pete screams for ice cream! The Just Chillin' ice cream truck is coming today and Pete the Cat can't wait. He runs as fast as he can to find the truck. It's getting late, but his friends need his help. Will Pete take a little time out of his day to help his friends? Follow Pete the Cat as he learns that it's always cool to be kind. From the authors of the #1 New York Times bestselling Pete the Cat series, James and Kimberly Dean, this book is reminiscent of Pete favorites like Magic Sunglasses and perfect for fans of Grumpy Monkey by Suzanne Lang. Don't miss Pete's other adventures, including Pete the Cat: I Love My White Shoes, Pete the Cat: Rocking in My School Shoes, Pete the Cat and His Four Groovy Buttons, Pete the Cat Saves Christmas, Pete the Cat and His Magic Sunglasses, Pete the Cat and the Bedtime Blues, Pete the Cat and the New Guy, Pete the Cat and the Cool Cat Boogie, Pete the Cat and the Missing Cupcakes, Pete the Cat and the Perfect Pizza Party, Pete the Cat: Crayons Rock!, Pete the Cat's Groovy Imagination, and Pete the Cat Plays Hide-and-Seek.